Desain Antar Muka Aplikasi Wisata dan Transportasi Sebagai Media Promosi Pariwisata di Surakarta - Nashih, Fikrun; Panindias, Asmoro Nurhadi (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Solo, a strategic city located on the axis of Central Java, is a city with high tourist and transit destinations because of its diverse tourism. This design uses the design thinking process method, starting from visual identity design, interface design to advertising design. While the data collection method used is a qualitative method in the form of observation, interviews, participatory and documentation analysis. Then for the design of the interface design using the principles of gestalt proximity and similarity. For the design of the ad design, it will use ambient media transit ads as a promotional medium. The result of the design is an online application platform in visual identity design, interface design, and advertising design for the application which is a platform that can help tourists in terms of accessing information and ordering tickets. And the results of the testing process can be used as an iterative process both in terms of application interface design or user experience in order to increase user satisfaction and application user effectiveness in accordance with community patterns in tourism.